O uso do aplicativo mobills para o controle de gastos na educação de jovens e adultos. - SOUSA, Jayne Neres de (Universidade Federal do Tocantins, 2023)
This work comes from a triad confluence that took place between the Education of Youths and Adults (EJA), the teaching of Financial Education and the Teaching Practice. The research problem consisted in knowing: In what way can the Mathematics teacher explore the situations of students' indebtedness in the Education of Young and Adults? The central objective of this research was the elaboration of a pedagogical proposal for Youth and Adult Education that characterize some aspects related to indebtedness. The nature of this research approaches the qualitative aspect with the development of bibliographic studies on the history of Youth and Adult Education. The materials of the National Financial Education Strategy (ENEF) served as a basis for Financial Education and to identify relevant aspects of indebtedness, a questionnaire was applied to students of EJA classes in a Municipal School and in a State High School. The data provided through the questionnaire show that the most evident debt situations were: bank loans and credit, and in the background by purchases in the credit card. The renegotiation was the main measure taken by the interviewees to solve the situations of indebtedness. The details of the situations of indebtedness were important for the elaboration of a contextualized pedagogical proposal directed to the education of Financial Education. For the elaboration of the pedagogic proposal the cell phone app Mobills of Control of Personal Expenses was used for the didactic organization of the classes.